A novel LC–MS approach for the detection of metabolites in DMPK studies. (October 2010) - Plumb, Robert S; Mather, Joanne; Little, David; Rainville, Paul D; Twohig, Marian; Harland, Gary; Kenny, Daniel J; Nicholson, Jeremy K; Wilson, Ian D; Kass, Ignatius J
Background: The profiling and quantification of drug metabolites in discovery and development bioanalysis studies is playing an increasingly important role in early candidate selection. Using a conventional tandem quadrupole mass spectrometer this activity normally requires several analytical runs to acquire the necessary analytical data.Results: In this article we present the use of a new tandem quadrupole mass spectrometer equipped with a novel collision cell design, which allows the rapid switching between multiple reaction monitoring and full-scan MS mode. This approach allowed for the collection of multiple reaction monitoring data and full-scan data with no loss in sensitivity, with analysis times in the 1–2 min range.Conclusion: A modified approach of using the multiple reaction monitoring data to trigger the acquisition of full scan MS/MS data is described, where the data is collected on the trailing edge of the LC–MS peak, thus improving data quality and throughput.